Economias de escala e escopo na previdência complementar fechada Brasileira - Marcelo Abi-Ramia Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This work identifies the existence of economies of scale and scope for the Brazilian complementary pension funds via quantitative tests on the administrative data base. It will be presented the literature review, descriptive statistics of the data base; a theoretical model on the existence of economies of scale in complementary pensions, the quantitative methods used, its results and the normative implications. Econometric results show that economies of scale on Brazilian complementary pensions are stronger than in the rest of the world.
Keywords: G23; J26; H55; 330; economies of scale; complementary pension funds; efficiency